Differential Game‑based Mimic Defense Scheduling Strategy in Power Systems - GU Liang; DI Ting; DU Feng (Taiyuan Ligong Daxue xuebao)
[Purposes] Traditional static defense can not meet the needs of power system in the face of diversified and growing Web security risks. Mimic defense technology is introduced to build the mimic defense architecture of power system to improve the active defense capability of power system. The process of network antagonism in the current study of scheduling strategy in mimic defense is discontinuous in time, and cannot make flexible decision in continuous real-time network offensive and defensive antagonism. [Methods] By introducing differential game, the state evolution equation of the executive body set was established, and the differential game scheduling model was constructed under the mimic defense architecture of power system. [Results] Simulation results show that compared with the traditional static architecture, the proposed method can improve the security by 65.9% and reduce the throughput by only 15%. At the same time, compared with the traditional mimic defense game model, the proposed model is improved in security by about 36%.